Closed‐system drug‐transfer devices in addition to safe handling of hazardous drugs versus safe handling alone for reducing healthcare staff exposure to infusional hazardous drugs - Gurusamy, Kurinchi Selvan (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness of closed‐system drug‐transfer of infusional hazardous drugs in addition to safe handling versus safe handling alone for reducing the exposure and risk of staff contamination to infusional hazardous drugs.